Analisis Perhitungan Harga Pokok Produksi CPO Pada PT Tunas Prima Sejahtera Samarinda - Nurmita Putri; Yunus Tete Konde; Muhammad Abadan Syakura (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
Nurmita Putri, 2019. Calculation Analyst Cost of CPO Production PT Tunas Prima Sejahtera Samarinda, under supervision of Mr. Yunus Tete Konde, as supervisor I and Mr. Muhammad Abadan Syakura, as supervisor II. This research aims to know how to calculate PT Tunas Prima Sejahtera’s cost of goods manufactured CPO so that selling of the company price higher than cost of production CPO. This research is using profit report from 2017 of PT Tunas Prima Sejahtera Samarinda. This research is using descriptive quantitative. The data is obtained by interview and documentation directly to the field. Data analysis methods in this study is the analysis of the cost of production by using the method full costing. Based on the analysis of data,it can be concluded that the factor cost of production CPO higher than the selling price of the company is the imposition of direct costs estate and indirect cost. It can be explained that the company in determining the cost of production of fruit own has not been fully effective and efficient.